Comparison of quantitative polymerase chain reaction, Kato-Katz and circulating cathodic antigen rapid test for the diagnosis of Schistosoma mansoni infection: A cross-sectional study in Kirinyaga County, Kenya - Benard Chieng (Current Research in Parasitology and Vector-Borne Diseases, 2021)
The current standard diagnostic tests for Schistosoma mansoni are the Kato-Katz and circulating cathodic antigen (CCA) techniques. However, these techniques have been documented to have several limitations that have a direct impact on schistosomiasis control programmes. Therefore, there is a need for more sensitive and specific tests for diagnosing schistosomiasis. This study compared the performance of quantitative polymerase chain reaction (qPCR), Kato-Katz, and point-of-care circulating cathodic antigen (POC-CCA) techniques in the diagnosis of S. mansoni infection in the Mwea irrigation scheme, Kirinyaga County in Central Kenya. We carried out a cross-sectional study on 357 individuals residing in four villages in the Mwea irrigation scheme. The participants provided urine and stool samples which were screened for S. mansoni infections using the three techniques. The prevalence of S. mansoni by each technique was calculated and 95% confidence intervals estimated using binomial regression model. Sensitivity and specificity were determined using 2 × 2 contingency tables and compared using the McNemar’s chi-square test. Positive and negative predictive values were also determined using the weighted generalized score chi-square test for paired data. The study showed that the prevalence of S. mansoni was 32.8%, 62.5% and 72.8% using Kato-Katz, POC-CCA and qPCR techniques, respectively. Further, when using Kato-Katz as a gold standard, POC-CCA sensitivity was 78.6% and specificity was 45.4%, while qPCR sensitivity was 97.4% and specificity was 39.2%. When using qPCR as the gold standard, Kato-Katz sensitivity was 43.8% and specificity was 96.9%, while POC-CCA sensitivity was 78.1% and specificity was 79.4%. Finally, when using the averaged results from the three techniques as the gold standard, the sensitivity was 41.6%, 79.4% and 92.5% for Kato-Katz, POC-CCA and qPCR, respectively, with a specificity of 100% for all techniques. Kato-Katz technique showed low sensitivity compared to the POC-CCA and qPCR despite it being the most commonly preferred method of choice to diagnose S. mansoni infections. qPCR showed superior sensitivity followed by POC-CCA, hence it can be used as an alternative or to confirm the results obtained by the Kato-Katz technique.